Aktivitas Antioksidan Teh Daun Ketapang (Terminalia catappa) - Widyastuti, Retno; Tari, Agustina Intan Niken; Asmoro, Novian Wely (Program Studi Teknologi Pangan, 2020)
The purpose of this study was to determine the antioxidant activity of fermented tea (black tea) with Ketapang leaves (Terminalia catappa) using two variations of leaf age, namely leaflets 1-3 and 4-5. The parameters observed were water content, pH, antioxidant activity (IC 50) and total phenol content of tea. Results showed that the antioxidant activity of young leaves (shoots 1-3) significantly higher than old leaves (shoots 4-5) but had lower total phenol and pH. In general, the character of Ketapang leaf tea products at shoots 1-5 has water content ranging from 5.55-5.58%, total phenol content of 22.63-28.97 mg / g EAG, and antioxidant activity (IC 50) of 6.27-6 .71 Âµg/ml and the pH of steeping water from 5.9 to 6.1.Â